2007
DOI: 10.1099/vir.0.82534-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of hantavirus carried by Apodemus peninsulae in Jilin, China

Abstract: To provide a better understanding of hantavirus epidemiology in China, Korean field mice (Apodemus peninsulae) and striped field mice (Apodemus agrarius) were captured in Jilin province, China, where haemorrhagic fever with renal syndrome (HFRS) is endemic. Hantavirus antigens were detected in eight of the 130 A. peninsulae individuals and in four of the 193 A. agrarius individuals by using an immunofluorescence assay. Partial S and M segments were amplified from all of the antigen-positive samples. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Following radiation of A. peninsulae, this latter group diversified into strain A16 in Shaanxi (Yao et al, 2001a), B78 in Shandong, H5 in Heilongjiang (Liang et al, 1994) and Amur-Soochong viruses in far-eastern Russia (Lokugamage et al, 2004) and South Korea (Baek et al, 2006). As A. agrarius and A. peninsulae are closely related (Liu et al, 2004;Serizawa et al, 2000) and often inhabit the same forest, HTNV is closely associated with both species (Zhang et al, 2007). The ancestor of clade III diversified into groups S2, S3 and S5, and then spread and further diversified following rodent migration to the north and the east.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following radiation of A. peninsulae, this latter group diversified into strain A16 in Shaanxi (Yao et al, 2001a), B78 in Shandong, H5 in Heilongjiang (Liang et al, 1994) and Amur-Soochong viruses in far-eastern Russia (Lokugamage et al, 2004) and South Korea (Baek et al, 2006). As A. agrarius and A. peninsulae are closely related (Liu et al, 2004;Serizawa et al, 2000) and often inhabit the same forest, HTNV is closely associated with both species (Zhang et al, 2007). The ancestor of clade III diversified into groups S2, S3 and S5, and then spread and further diversified following rodent migration to the north and the east.…”
Section: Discussionmentioning
confidence: 99%
“…The first clade consisted of viruses (group S4) derived only from A. agrarius in Guizhou. The second clade comprised two groups (S1 and S6), derived mainly from humans, A. agrarius and A. peninsulae in north-eastern China (Sun et al, 2001;Wang et al, 2000;Zhang et al, 2007), as well as from far-eastern Russia (Lokugamage et al, 2004) and South Korea (Baek et al, 2006;Lee et al, 1978), both of which share borders with China. The third clade included three groups (S2, S3 and S5), derived mainly from A. agrarius in HFRS endemic areas of China including Guizhou.…”
Section: Phylogenetic Relationship Of Htnv From Guizhou With Those Frmentioning
confidence: 99%
“…Consistent with the geographic distribution of A. agrarius mice, HTNV has been found in all Chinese provinces except Xinjiang ( 11 , 12 , 22 , 28 , 32 ). In addition to A. agrarius mice, HTNV has been also found in Apodemus peninsulae mice in northeastern China ( 33 ). Genetic analysis of the small (S) and medium (M) genome segments suggested that at least 9 distinct lineages of HTNV are circulating in China (Figure 3) ( 11 , 32 ).…”
Section: Hantavirus Isolatesmentioning
confidence: 99%
“…3). Although a particular hantavirus species has been reported to be associated with several closely related host species [Lee and Johnson, 1982;Childs et al, 1994;Plyusnin et al, 1994b;Morzunov et al, 1998;Monroe et al, 1999;Plyusnin and Morzunov, 2001;Sun et al, 2005;Zhang et al, 2007b], there are only a few known cases of one rodent species being the bona fide reservoir host of two distinct hantaviruses . Thus, our results suggest that the reed vole M. fortis is the reservoir host for VLAV (including Fusong strains described here) and M. maximowiczii is the reservoir host of KHAV (including Yakeshi strains described here).…”
Section: Discussionmentioning
confidence: 96%